Regulation of Female Germline Specification via Small RNA Mobility in Arabidopsis. Issue 9 (23rd July 2020) - Su, Zhenxia; Wang, Nannan; Hou, Zhimin; Li, Baiyang; Li, Dingning; Liu, Yanhui; Cai, Hanyang; Qin, Yuan; Chen, Xuemei
Abstract : Intricate spatial restriction of tasiR-ARF biogenesis, together with tasiR-ARF mobility, enables cell-cell communication in MMC differentiation. Abstract: In the ovules of most sexually reproducing plants, one hypodermal cell differentiates into a megaspore mother cell (MMC), which gives rise to the female germline. Trans -acting small interfering RNAs known as tasiR-ARFs have been suggested to act non-cell-autonomously to prevent the formation of multiple MMCs by repressing AUXIN RESPONSE FACTOR3 ( ARF3 ) expression in Arabidopsis ( Arabidopsis thaliana ), but the underlying mechanisms are unknown. Here, we examined tasiR-ARF-related intercellular regulatory mechanisms. Expression analysis revealed that components of the tasiR-ARF biogenesis pathway are restricted to distinct ovule cell types, thus limiting tasiR-ARF production to the nucellar epidermis. We also provide data suggesting tasiR-ARF movement along the mediolateral axis into the hypodermal cells and basipetally into the chalaza. Furthermore, we used cell type-specific promoters to express ARF3m, which is resistant to tasiR-ARF regulation, in different ovule cell layers. ARF3m expression in hypodermal cells surrounding the MMC, but not in epidermal cells, led to a multiple-MMC phenotype, suggesting that tasiR-ARFs repress ARF3 in these hypodermal cells to suppress ectopic MMC fate. RNA sequencing analyses in plants with hypodermally expressed ARF3m showed that ARF3 potentially regulates MMC specification through phytohormone pathways. Our findings uncover intricate spatial restriction of tasiR-ARF biogenesis, which together with tasiR-ARF mobility enables cell-cell communication in MMC differentiation.